A GeV-TeV particle component and the barrier of cosmic-ray sea in the Central Molecular Zone - Xiaoyuan Huang (Nature Portfolio, 2021)
Galactic center is one of the most important cosmic-ray sources. Here, the authors show GeV-TeV cosmic ray density in the central molecular zone is lower than the cosmic ray sea component, suggesting presence of high energy particle accelerator at the galactic center and existence of barrier.